Straw decay and its effect on disposal and utilization : proceedings of a Symposium on Straw Decay and Workshop on Assessment Techniques, held at Hatfield Polytechnic, April 10-11th 1979 - Grossbard, E. (Chichester ; New York : J. Wiley, 1979)
This is the proceedings of a Symposium on Straw Decay and Workshop on Assessment Techniques, held at Hatfield Polytechnic, April 10-11th 1979 . The total area of crops producing straw is dominated by barley and wheat with very much smaller areas of oats.
"A Wiley-Interscience publication."
Includes bibliographical references and index.
II 16/01/2019
Loans
Keywords: Straw